210k views
2 votes
Solve the following system:

-2x + 2y + z = 14
3x – 2y +z = -5
-x + y - 2z = -8
PLEASE HELP

1 Answer

4 votes

Answer:

Read explanation

Explanation:

Use elimination

Add them all up

y = 1 ( everything else cancels )

-2x + 2(1) + z = 14

3x - 2(1) + z = -5

-x +(1) - 2z = -8

simplify

-2x + z = 12

3x + z = -3

-x -2z = -9

U can't use elimation because it would turn into 0 = 0

change last equation

x + 2z = 9

x = -2z + 9

plug that in

-2(-2z+9) + z = 12

3(-2z+9) + z = -3

-(-2z+9) - 2z = -9

4z - 18 = 12

-6z + 27 + z =-3

2z - 9 - 2z = -9

simplify

4z = 30

-5z = -30

0 = 0

z = 6

y = 1

x = -3

User Vineet Choudhary
by
4.5k points